SINTESIS ANALOG 2-PIRAZOLIN DARI KALKON INTI NAFTALEN DAN UJI AKTIVITASNYA SEBAGAI ANTIBAKTERI - Hayati, Fitrah; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazolines have been reported to possess many of interesting biological activities suchas antibacterial, antitumor, antioxidant, anti-inflammatory, antimalarial, anticancer, andanticonvulsant activity. In this research, an analog pyrazoline 5-(4-chlorophenyl)-3-(naphthalene-1-yl)-4,5-dihydro-1H-pirazol was synthesized by the reaction between 1-naphthyl chalcones and hydrazine hydrate using glacial acetic acid as catalyst undermicrowave irradiation. The compound showed a good yield, and then was characterizedby UV, IR and 1 H-NMR spectroscopy. The antibacterial activity of this compound wasdetermined using agar diffusion method against the bacteria Escherichia coli,Salmonella typi, Bacillus subtilis and Staphylococcus aureus. The antibacterial activitywere classified as very weak at concentrations of 10, 30 and 50 Î¼g/disk with a diameterof inhibition produced of 6,2 â 8,1 mm.